Katie, sprinkles & surprises - Simon, Coco (Simon, Coco. Cupcake diaries, 2013)
When Katie learns that her mother's new boyfriend is her math teacher, Jeff Green, Katie is accused of getting special treatment in class, and it's the Cupcake Club to the rescue to help Katie deal with the rumors and the changes in her life.